2014
DOI: 10.1039/c4ta01554a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric figure of merit in p-type Bi0.48Sb1.52Te3 alloy with WSe2 addition

Abstract: P-type Bi 0.48 Sb 1.52 Te 3 alloys added with WSe 2 were achieved via the zone melting method. The electrical performance was improved due to the increased carrier concentration, while the lattice thermal conductivity was simultaneously decreased, mainly due to the numerous types of nanoprecipitates produced, such as the second phase, antisite substitution and interfaces with different scales. As a result, a 23% improvement in the thermoelectric figure of merit zT was obtained with the addition of WSe 2 , maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…2 Among numerous thermoelectric materials, bismuth telluride (Bi 2 Te 3 )based ingots are the most well-established thermoelectric materials at room temperature and almost dominate the industry at present, 3,4 because of the increasing demand for electronic cooling and thermoelectric power generation for low-temperature waste heat. 2 Among numerous thermoelectric materials, bismuth telluride (Bi 2 Te 3 )based ingots are the most well-established thermoelectric materials at room temperature and almost dominate the industry at present, 3,4 because of the increasing demand for electronic cooling and thermoelectric power generation for low-temperature waste heat.…”
Section: Introductionmentioning
confidence: 99%
“…2 Among numerous thermoelectric materials, bismuth telluride (Bi 2 Te 3 )based ingots are the most well-established thermoelectric materials at room temperature and almost dominate the industry at present, 3,4 because of the increasing demand for electronic cooling and thermoelectric power generation for low-temperature waste heat. 2 Among numerous thermoelectric materials, bismuth telluride (Bi 2 Te 3 )based ingots are the most well-established thermoelectric materials at room temperature and almost dominate the industry at present, 3,4 because of the increasing demand for electronic cooling and thermoelectric power generation for low-temperature waste heat.…”
Section: Introductionmentioning
confidence: 99%
“…The BiSbTe matrix shows typical electrical conductivity of 1.0 × 10 5 S/m at room temperature. This value is slightly smaller than those of samples prepared by zone melting [16,17,27,33], but higher than those of samples prepared by SPS [28]. After introducing additional graphene, the electrical conductivity slightly enhances for x = 0.05, and then decreases with further increasing graphene content.…”
Section: Resultsmentioning
confidence: 68%
“…Nanocomposite has been suggested to be an effective approach to synergistically tune the electrical and the thermal properties by introducing second phase nanoparticles into the matrix [12][13][14][15][16][17][18]. Lots of materials, such as ZnAlO, WSe 2 and silver, have been used as second phase nanoparticles to enhance the TE performance of Bi 2 Te 3 -based alloys [16][17][18][19]. Not all composites show synergistic optimization…”
Section: Introductionmentioning
confidence: 99%
“…14 Recently, G. J. Tan et al reported that Sn self-compensation can effectively reduce the Sn vacancies and decrease the hole carrier density. 19,20 The obtained samples show enhanced power factors (S 2 s) with a maximum value of 30.5 mW cm À1 K À2 at 823 K, which is the highest reported value in the SnTe alloys so far. With further modication of the band structure by Cd, Hg, or Mg alloying in SnTe, the Seebeck coefficient of SnTe is greatly enhanced and the maximum ZT value is larger than 1.2 above 860 K. 11,[15][16][17] A recent theoretical study has shown that the high p-type carrier concentration in SnTe is dominated by the intrinsic negatively charged Sn vacancy (V Sn 2À ), which always has a negative formation energy regardless of the growth condition, and alloying with Pb can inhibit the formation of cation vacancy.…”
Section: Introductionmentioning
confidence: 72%